Transforming meat waste into sustainable corneal keratoplasty models - Mobin, Ayman; Hashem, Zayd; Corridon, Peter R. (Frontiers in Bioengineering and Biotechnology, 2025)
With a rapidly global population, there is a critical need to enhance food production and waste management. This necessity is driving opportunities for sustainable integrated food chains committed to biovalorization and circular bioeconomic practices. One approach that aligns with this vision relies on sustainable tissue engineering, which offers opportunities to leverage food systems in the search for natural biomaterials from agricultural waste. In this perspective, we propose utilizing common meat waste sources, often associated with a high environmental footprint, to develop tissue graft models. These models reduce agricultural waste, decrease the reliance on animal testing, and support both biovalorization and medical innovation. Specifically, we explore a unique approach to generate corneal transplantation models completely from discarded components of the meat food chain, using the eyes and bladders. This strategy involves creating keratoplasty models by reseeding the decellularized extracellular matrix (dECM), encompassing three major corneal regions: the epithelium, stroma, and endothelium. Interestingly, these scaffolds can be recellularized with cellular lineages derived from stem niches harvested from urine. This approach integrates waste management with regenerative medicine, fostering sustainable advancements in tissue engineering.